Space and Planetary Resources - Abbud-Madrid, Angel; Neal, Clive; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Space and Planetary Resources is an international journal in English that publishes high quality original research articles and timely reviews in the interdisciplinary field of space and planetary resources. The SPR journal provides an integrated platform to publish novel data and findings, as well as innovative concepts, models, and technological advances related to various aspects particularly relevant to extraterrestrial resource exploration/prospecting, extraction, processing, and utilization, as well as economic, environmental, legal, and policy issues. The journal also covers related scientific research into the origin and evolution of planetary resources, space robotics, manufacturing, construction, and infrastructure.
Keywords: Geology; Geology